2020
DOI: 10.31234/osf.io/k97z5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Back to Basics: The Importance of Measurement Properties in Biological Psychiatry

Abstract: Biological psychiatry is a major funding priority for organizations that fund mental health research (e.g., National Institutes of Health). Despite this, some have argued that the field has fallen short of its considerable promise to meaningfully impact the classification, diagnosis, and treatment of psychopathology. This may be attributable in part to a paucity of research about key measurement properties (“physiometrics”) of biological variables as they are commonly used in biological psychiatry research. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
7
2
Order By: Relevance
“…However, given that this bias only was seen in two of the nine symptoms and that effect sizes were small, this is likely not a hugely influential issue for CRP and the PHQ-9. It is worth note that, while small, the effect Hierarchical Inflammatory Phenotypes of Depression Moriarity et al 12 sizes observed in this study are larger than the average effect sizes found in a recent metaanalysis (52), highlighting the possibility that structural equation modeling's ability to correct for measurement error might deattenuate downward-biased effect sizes resulting from unreliable measures (53,54). Further, if CRP is a truly a unique predictor of both latent depression (i.e., the variance shared among depression symptoms) and individual symptoms, larger effect sizes might be the result of selecting a model that more closely matches the naturally-occurring relations (resulting in less error).…”
Section: Discussioncontrasting
confidence: 72%
“…However, given that this bias only was seen in two of the nine symptoms and that effect sizes were small, this is likely not a hugely influential issue for CRP and the PHQ-9. It is worth note that, while small, the effect Hierarchical Inflammatory Phenotypes of Depression Moriarity et al 12 sizes observed in this study are larger than the average effect sizes found in a recent metaanalysis (52), highlighting the possibility that structural equation modeling's ability to correct for measurement error might deattenuate downward-biased effect sizes resulting from unreliable measures (53,54). Further, if CRP is a truly a unique predictor of both latent depression (i.e., the variance shared among depression symptoms) and individual symptoms, larger effect sizes might be the result of selecting a model that more closely matches the naturally-occurring relations (resulting in less error).…”
Section: Discussioncontrasting
confidence: 72%
“…Our work follows recent calls for increasing attention to measurement reliability as a crucial determinant of statistical power in psychology and the neurosciences (Fröhner, Teckentrup, Smolka, & Kroemer, 2019; Hedge, Powell, & Sumner, 2018; Moriarity & Alloy, 2021; Zuo, Xu, & Milham, 2019). Measurement reliability is of key importance when addressing clinically-relevant questions involving individual-level predictions such as predicting treatment success from extinction (e.g., Lange et al, 2020; Scheveneels, Boddez, Vervliet, & Hermans, 2016) or biomarkers (Cano-Catala et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…However, a remarkable amount of predictions were non-significant - which was particularly true for CS discrimination in SCRs and BOLD. This may be explained by difference scores (i.e., CS+ minus CS-) being generally less reliable (Lynam, Hoyle, & Newman, 2006) due to a subtraction of meaningful variance (Moriarity & Alloy, 2021) particularly in highly-correlated predictors (Thomas & Zumbo, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations